Biometric security and privacy : opportunities & challenges in the big data era - Jiang, Richard; Al-madeed, Somaya; Bouridane, Ahmed; Crookes, Danny, 1956-; Beghdadi, A. (Springer, 2017)
This book highlights recent research advances on biometrics using new methods such as deep learning, nonlinear graph embedding, fuzzy approaches, and ensemble learning. Included are special biometric technologies related to privacy and security issues, such as quality issue, biometric template protection, and anti-spoofing. The book also focuses on several emerging topics such as big data issues, mobile biometrics and multispectral biometrics, and includes a number of new biometrics such as vein pattern, acoustic biometrics, eye-blinking EOG, ECG, gait and handwriting. Authors also show how to use biometrics in cyber security applications and its relevant legal matters under EU legislation. The contributors cover the topics, their methods, and their applications in depth.
Includes index.
Keywords: Biometric identification.; Big data.; Artificial intelligence.; elektronické knihy; electronic books